Pengaruh Tunjangan Kinerja dan Beban Kerja terhadap Kinerja Pegawai di Kantor Dinas Sosial Kota Surabaya - Nurmansyah, Andre (Al Makki Publisher, 2025)
This study aims to examine the influence of performance allowance and workload on the performance of civil servants at the Social Affairs Office of Surabaya City. A quantitative approach with a multiple linear regression design was applied. Data were collected from 40 civil servants through a structured questionnaire and analyzed using SPSS software. The results reveal that performance allowance has a significant positive effect on employee performance, while workload has a significant negative effect. The regression model met all classical assumptions, demonstrating its validity and reliability. These findings highlight the importance of designing effective compensation systems and managing workload distribution to improve employee performance in the public sector. The study provides practical insights for government institutions to develop human resource strategies that are both fair and performance-driven. Further research is recommended to include additional internal variables, such as motivation or job satisfaction, to build a more comprehensive model of civil servant performance in public administration.